The Impact of Sustainable Finance and Green Bond Implementation on Firm Value and Investor Trust in the Manufacturing Industry in Central Java - Rahmiyati, Nekky; Somodiharjo, Kadari; Hariyani , Diyah Santi (Westscience Press, 2025)
This study examines the impact of Sustainable Finance and Green Bond Implementation on Firm Value and Investor Trust in the manufacturing industry in Central Java. Employing a quantitative approach with 143 samples, data were collected using a Likert scale (1–5) and analyzed through Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results reveal that both Sustainable Finance and Green Bond Implementation significantly enhance Firm Value and Investor Trust. Green Bond Implementation, in particular, demonstrates a stronger influence on these variables, highlighting its critical role in driving sustainable development and corporate credibility. Model fit indices and predictive relevance metrics confirm the robustness of the proposed model. These findings underscore the importance of sustainability in corporate finance and its implications for stakeholder relationships. The study provides valuable insights for companies and policymakers seeking to integrate sustainability into their financial strategies.